Minithoracoscopy for Pleural Effusions - RA Malthaner; RI Inculet (Canadian Respiratory Journal)
The current management of pleural disease often requires direct visualization and biopsy of the pleural space using thoracoscopy. A diagnostic and therapeutic approach to pleural disease is described that uses a new 2 mm rigid thorascope. The technique allows complete visualization, biopsy and drainage of the pleural space with rapid recovery and minimal pain.